Care as a Contemporary Paradox in a Global Market - Rogerson, Ann; Morgan, Mandy; Coombes, Leigh (Massey University, 2011)
The contemporary mother faces difficult choices when deciding whether to be either a ‘stay at home’ or a ‘working mother’. Conflicting discourses of good and bad mothering revolve around a political divide under pressure, one that territorialises the public and private domains. Gilligan (1982) famously highlighted the existence of these domains by challenging Kohlberg’s findings that men were endowed with higher moral reasoning powers than women. Disappointed by what she identified as the masculinist bias of Kohlberg’s work, Gilligan conducted her own research, finding that men and women reasoned differently but equitably. Gilligan’s thesis now theoretically informs a feminist ethics of care that has reputedly transformed political spatial boundaries of the public and private domains, domains traditionally gendered as masculine and feminine. Yet the ‘care’ that Gilligan has drawn our attention to is seemingly a new phenomenon. Appearing in language around the same time as the birth of Gilligan’s feminist ethics and indeed amidst the growing dilemma of the working mother, this care shows no visible sign of its maternal origins. In this paper, I attempt to define and locate care amidst the dismantling of the spatial divide that separates the public and private, a dismantling that coincides with the commodification of care within a global market.
This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivs 3.0 Unported License
Keywords: Care; Feminist; Ethics; Sexual difference; Public and private domains; Mothering